DNA FINGERPRINTING OF INDIAN POTATO CULTIVARS BY INTER SIMPLE SEQUENCE REPEATS (ISSRS) MARKERS - G, Vanishree; Patil, Virupaksh U; Kardile, Hemant; Bhardwaj, Vinay; Singh, Rajendra; Chakrabarti, S K (Potato Journal, 2016)
Commercial scale fingerprinting of potato cultivars need speedy and reliable methods having the ability to distinguish between large numbers of genotypes. Present study highlights the potentiality of using ISSR-PCR for fingerprinting. In these study 11 multi loci ISSR markers were evaluated in 47 commercial Indian potato cultivars and the complex band profiles generated were highly reproducible. A total of 68 distinct alleles were obtained with number varying from 3 (ISSR UBC079) to 9 (ISSR 827). The average fragments per (AM) marker and per genotype (AG) were 6.1 and 1.43 respectively with a total of 47 polymorphic fragments. Rp value varied from 4.17 (ISSR UBC079) to 12.26 (ISSRHB-10). Theaverage Rp was 7.60 per ISSR primer and dendrogram analysis showed that Indian potato cultivars, placed into three broadclusters which were in concordance with the Principle Component (PCO) analysis. Similarity coefficient varied from 0.82 to as high as 0.98 and PIC value of the markers ranged from 0.16 (ISSR UBC079) to 0.35 (ISSR 7). Furthermore, use of these markers in combination need to be checked for distinguishing all cultivars. The study revealed that ISSR-PCR technique seems to have potential for the large-scale and systematic fingerprinting of potato cultivars with added number of ISSR markers and high resolving techniques to unearth the diversity present in the Indian potato cultivars.